Inventing superstition : from the Hippocratics to the Christians - Martin, Dale B., 1954- (Harvard University Press, 2004)
"Dale Martin provides the first detailed genealogy of the idea of superstition, its history over eight centuries, from classical Greece to the Christianized Roman Empire of the fourth century C.E. With reference to the writings of philosophers, historians, and medical teachers he demonstrates that the concept of superstition was invented by Greek intellectuals to condemn popular religious practices and beliefs, especially the belief that gods or other superhuman beings would harm people or cause disease. Tracing the social, political, and cultural influences that informed classical thinking about piety and superstition, nature and the divine, Inventing Superstition exposes the manipulation of the label of superstition in arguments between Greek and Roman intellectuals on the one hand and Christians on the other, and the purposeful alteration of the idea by Neoplatonic philosophers and the Christian apologists in late antiquity."--Jacket.